A novel temporal filtering strategy for functional MRI using UNFOLD - Domsch, Sebastian; Lemke, Andreas; Weingärtner, Sebastian; Schad, Lothar R. (NeuroImage, 2012)
A major challenge for fMRI at high spatial resolution is the limited temporal resolution. The UNFOLD method increases image acquisition speed and potentially enables high acceleration factors in fMRI. Spatial aliasing artifacts due to interleaved k-space sampling are to be removed from the image time series by temporal ﬁltering before statistical mapping in the time domain can be carried out. So far, low-pass ﬁltering and multiband ﬁltering have been proposed. Particularly at high UNFOLD factors both methods are non-optimal. Lowpass ﬁltering severely degrades temporal resolution and multi-band ﬁltering leads to temporal autocorrelations affecting statistical modelling of activation. In this work, we present a novel temporal ﬁltering strategy that signiﬁcantly reduces temporal autocorrelations compared to multi-band ﬁltering. Two datasets (ﬁngertapping and resting state) were post-processed using the proposed and the multi-band ﬁlter with varying set-ups (i.e. transition bands). When the proposed ﬁltering strategy was used, a linear regression analysis revealed that the number of false positives was signiﬁcantly decreased up to 34% whereas the number of activated voxels was not signiﬁcantly affected for most ﬁlter parameters. In total, this led to an effective increase in the number of activated voxels per false positive for each ﬁlter set-up. At a signiﬁcance level of 5%, the number of activated voxels was increased up to 41% by using the proposed ﬁltering strategy.